PELATIHAN PEMBUATAN DESIGN LANDING PAGE CANVA UNTUK MENDUKUNG PENJUALAN UMKM DI KECAMATAN PESANGGRAHAN JAKARTA SELATAN - Purwanto Purwanto; Rusdah Rusdah; Indra Nugraha; Yulianawati Yulianawati; Sri Wahyuningsih (LPPM Universitas Bina Bangsa, 2023)
The majority of MSME actors in Pesanggrahan sub-district, South Jakarta are mothers who do not work and have no other activities apart from being housewives. Usually they have businesses other than being housewives, namely producing food, drink and handicraft products. The majority of these mothers do not have sufficient education to start an entrepreneur. Marketing is only carried out traditionally or conventionally in the area, so that most of the products are only sold in the area where they live. To make their business grow, they need to promote the products they have produced so that these products can be marketed widely. The aim of this training program is to provide knowledge and business skills to business actors while utilizing the Canva application to promote online, so that MSME products can successfully enter every market in Indonesia. The training material explains how to create a landing page design using the Canva application using a smartphone. Most of the MSME mothers do not understand and master the use of smartphones and are included in the group of people who are unable to use technology, so the team of lecturers from Budi Luhur University who in this case participate as companions for the mothers in supporting them to expand their business by providing training on creating Canva landing page designs. Training is carried out face-to-face at the Computer Laboratory of Budi Luhur University. In this training, participants directly practice in front of a computer and also use the smartphone they own. At the end of the training session participants were asked to fill out a questionnaire containing the results of the training they attended. From the evaluation results, 100% of the training participants stated that the training material would be useful in the future and 82.6% stated that the resource persons/facilitators presented material that was easy for the participants to understand